GAMBARAN KEJADIAN KURANG ENERGI KRONIK DAN POLA MAKAN WANITA USIA SUBUR DI DESA PESINGGAHAN KECAMATAN DAWAN KLUNGKUNG BALI 2014 - Patricia Stephanie; Sari Komang Ayu Kartika (Universitas Udayana, 2016)
Chronic energy deficiency in pregnant women persists as health problem in Indonesia. The prevalence of pregnant woman with chronic energy deficiencyin Indonesia is 21,6%. Based on data in Puskesmas Dawan I, the prevalence of pregnant women with chronic energy deficiency takes 6,2%. To prevent the risk of chronic energy deficiency in pregnant women before pregnancy, reproductive age women should have good nutritional status, for instance upper arm circumference is 23,5 cm minimally. The aim of this research is to find out the description of chronic energy deficiency incidence, knowledge of nutrition and the impact of chronic energy deficiency, and consumption pattern in reproductive age women at Pesinggahan Village. This research may give suggestions to UPTD Puskesmas Dawan I to take effective actions in giving information and other health promotions. In addition, it may improve the knowledge of reproductive age women about balance diet, food selection, meal frequency, food portion, and the impact of chronic energy deficiency. Improvement of the knowledge hopefully can improve the behavior and meal frequency of pregnant women. This research is a cross-sectional descriptive study with total sample 47 respondents that consist of married reproductive age women in Pesinggahan Village. Data was collected by questionnaire. The collected data would be analyzed in descriptive way that presented in data tabulation and explained by table and narration. The result showed that 7 respondents (14,9%) got chronic energy deficiency and 40 people (85,1%) did not. The 91,5% of fertile-age women had good behavior whereas poor behavior one took 8,5%. Two respondents (6,9%) with income above the minimum wages got chronic energy deficiency and 5 respondents (10,6%) with income below the minimum wages got chronic energy deficiency. 4 respondents (9,3%) with good behavior got chronic energy deficiency whereas 3 respondents (75%) with poor behavior got chronic energy deficiency.